Atresia of the right coronary arterial ostium with a left ventricular fistula: A case report. Issue 2 (August 2022) - Suzuki, Takanori; Miyagawa-Tomita, Sachiko; Saito, Kazuyoshi; Yoshikawa, Tetsushi; Kawai, Satoru; Yasuda, Kazushi
Abstract: We describe the case of a young patient with atresia of the right coronary arterial ostium with left ventricular fistula. This was suspected from the abnormality detected on a 12‑lead electrocardiogram (ECG) during a school examination at the time of admission to junior high school and echocardiography findings. This disease may occur due to abnormalities in several molecules that are essential for coronary artery development. In cases of ECG abnormality, and unexplained aortic valve regurgitation and coronary artery abnormalities on echocardiography are detected, this disease should be suspected. Learning objective: Coronary artery anomalies have been identified in coronary angiograms. Herein, we describe the case of a young patient with atresia of the right coronary arterial ostium with left ventricular fistula. This disease may be caused by abnormalities in several molecules that are essential molecule for coronary artery development.